An analysis of the relationship between moral judgment, racism,and activism - Zini Moreira Aresi, Paula; de Lucena Moreira, Pollyana (Pensando Psicología, 2023)
This research, which has a quantitative design, sought to investigate the relationship between moral judgment and political action to reduce prejudice in society, emphasizing political activism and modern racism. It started from the idea that moral judgment is linked to the conceptions that people have about social reality and about their distinct groups, and that such conceptions can affect the way people act politically, or their intention to act. A total of 130 Brazilians participated in this research, who answered an online form with measures that aimed to assess moral judgment, modern racism, political ideology, willingness to take actions to reduce prejudice and promote diversity, and the intention to engage in political action in the form of activism. Data were analyzed using IBM SPSS and it was found that conventional moral judgment was related to political conservatism, with a higher rate of racism and a lower willingness to engage in political actions aimed at reducing prejudice and promoting diversity, and with a lower intention of engaging in activist actions, even those aimed at defending the group itself. Based on the results, it can be concluded that qualitatively different forms of moral judgment, at the level of individual thinking, are associated with qualitatively different ways of thinking about society and acting in it.
Keywords: Activism; political ideology; morality; racism